Analisis Perencanaan Sheet Pile pada Tanggul Sungai (Studi Kasus : Sungai Lungun, Sabanar Baru, Kabupaten Bulungan) - Hasrullah; Elia, Sebanya; Novianto, Dandung (Indonesian Society of Applied Science, 2021)
This study was conducted to identify thecauses of landslides on river embankments. This studu aims to determine the value of the slope safety factor and to plan the dimensions of sheet pile reinforcement and stability on the slopes of the Lungun River. This study used the Fellenius method to analyze the stability of the existing slope, the design principle of sheet piles in anchors located on cohesive soil with the free end method, and also with the help of a computer technology program, namely Plaxis application program. From the results of the analysis and calculations, it was concluded that the value of the safety factor on the slopes of the Lungun River using the manual calculations of the Fellinus Method. A value of 1.470 was obtained and a calculation using the Plaxis 2D V.8.2 program obtained a value of 1.1092. For the solutions to landslides on the slopes of the Lungun River, the dimensions of sheet pile reinforcement obtained from the calculation were using a concrete sheet pile type W-400 A 1000 with a depth of 10 m plus anchor recognition at a depth of 1 m from the ground surfaces which was connected by a steel tie rod 7 cm along 14 m to a concrete anchor block with height of 1.5 m and thickness of 5 cm which was embedded 0.5 m from the ground surface, so that the value of safety factor that was calculated using the Plaxis 2D V.8.2 program was 3.5814.